MEASUREMENT OF THE TRIPLE-GLUON VERTEX FROM 4-JET EVENTS AT LEP - Abreu, P; Adam, W; Adye, T; Agasi, E; Aleksan, R; Alekseev, G; Algeri, A; Allen, P; Almehed, S; Alsvaag, S; Amaldi, U; Andreazza, A; et al. (1993)
From the combined data of 1990 and 1991 of the DELPHI experiment at LEP, 13057 4-jet events are obtained and used for determining the contribution of the triple-gluon vertex. The relevant variables are the generalized Nachtmann Reiter angle θNR* and the opening angle of the two least energetic jets. A fit to their two-dimensional distribution yields Mathematical expression where CA/CF is the ratio of the coupling strength of the triple-gluon vertex to that of gluon bremsstrahlung from quarks, and NC/NA, the ratio of the number of quark colours to the number of gluons. This constitutes a convincing model-independent proof of the existence of the triple-gluon vertex, since its contribution is directly proportional to CA/CF. The results are in agreement with the values expected from QCD:CA/CF=2.25, and NC/NA=3/8. © 1993 Springer-Verlag.